2019
DOI: 10.3892/ol.2019.10139
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of the HACE1 gene promoter inhibits the proliferation of human liver cancer cells

Abstract: HECT domain and ankyrin repeat containing E3 ubiquitin protein ligase 1 (HACE1) is frequently downregulated or lost in numerous types of cancer, including liver cancer. The aim of the present study was to examine whether demethylation of the HACE1 gene could inhibit tumour progression. The expression of HACE1 was detected in liver cancer cell lines. Clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated (Cas)-based demethylation single guide RNAs for the HACE1 gene promoter were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In the present study, propofol >120 µmol/l exhibited little inhibition; however, the specific underlying mechanism requires further investigation, although it was hypothesized that the concentration of propofol reached saturation at 120 µmol/l. HACE1 is frequently downregulated or lost in numerous types of tumor, such as lung and liver cancer, and acts as a tumor suppressor by ubiquitinating OPTN and activating selective autophagy (18,24). The study found that propofol promoted HACE1 expression levels by demethylating HACE1 gene promoter, which activated HACE1-OPTN axis-mediated autophagy.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the present study, propofol >120 µmol/l exhibited little inhibition; however, the specific underlying mechanism requires further investigation, although it was hypothesized that the concentration of propofol reached saturation at 120 µmol/l. HACE1 is frequently downregulated or lost in numerous types of tumor, such as lung and liver cancer, and acts as a tumor suppressor by ubiquitinating OPTN and activating selective autophagy (18,24). The study found that propofol promoted HACE1 expression levels by demethylating HACE1 gene promoter, which activated HACE1-OPTN axis-mediated autophagy.…”
Section: Discussionmentioning
confidence: 87%
“…HACE1 is frequently downregulated or lost in numerous types of tumor, such as lung and liver cancer, and acts as a tumor suppressor by ubiquitinating OPTN and activating selective autophagy ( 18 , 24 ). The study found that propofol promoted HACE1 expression levels by demethylating HACE1 gene promoter, which activated HACE1-OPTN axis-mediated autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First identified in 2004, HECT domain and ankyrin repeat containing E3 ubiquitin protein ligase 1 (HACE1; 909 residues) has been shown to take part in various cellular processes. For example, HACE1 is best known as a tumor suppressor as altered HACE1 expression levels have been observed in various cancers including colorectal, breast, liver, kidney, osteosarcoma, lymphoma and gastric cancer [50][51][52][53][54]. HACE1 contains six ankyrin repeats near its N-terminus that likely take part in HACE1-substrate recognition and protein-protein interactions (Figure 2).…”
Section: Hace1 a Prominent Tumor Suppressor With Dual Functionmentioning
confidence: 99%
“…Low expression levels of HACE1 have also been observed in other cancer cell lines. For instance, it was found that the methylation of the HACE1 promoter resulted in decreased HACE1 expression in liver cancer cells, which in turn decreased HACE1's ability to ubiquitylate its identified substrates optineurin (OPTN) and microtubule-associated proteins 1A/1B light chain 3B protein [53]. Many different substrates of HACE1 have been identified to date (summarized in [4]), including β2-adrenergic receptor (ß2AR) [58], OPTN [59], retinoic acid receptor beta (RAR-β) [57], tumor necrosis factor receptor-2 (TNFR2) [60], and various Ras-related [55]), which is likely involved in HACE1 substrate binding and recognition, and a HECT domain (HECTN-lobe in green, HECTC-lobe in blue; PDB 6JX5 [35]) found at HACE1's C-terminus that is required of ubiquitylation activity.…”
Section: Hace1 a Prominent Tumor Suppressor With Dual Functionmentioning
confidence: 99%